“Brand New World” - The Brand Values of Nations - Papp-Váry, Árpád Ferenc (Marketing & Menedzsment, 2019)
„According to some estimates, brand value could be as much as one-third of the entire value of global wealth (Anholt 2005, page 2). No wonder that we can visualize a time when the marketing concept itself will become obsolete, to be replaced by a new concept called “branding” (Ries - Ries 2002, page x). But what is a “brand”? And what is a “country brand”? Is it possible to measure somehow the brand values of nations?